Pengembangan Media Scrapbook untuk Pembelajaran Menulis Teks Biografi pada Siswa SMA Kelas X - Isnain, Agustin; Alfin. N.H, Maulidia Tifani (University of Brawijaya, 2025)
This study aims to find out how to develop and test the feasibility of scrapbook media for learning to write high school biography texts. The development of Scrapbook media is viewed from the aspect of media display and media programming. This research and development was carried out by adapting the ten stages of the development procedure from Born Gall, but simplified to just six stages, namely needs analysis, planning, production, expert validation, revision, and limited trials. Data processing was carried out by calculating the validation scores from media experts I and media experts II, as well as student response questionnaire scores. The trial was conducted on class X MIPA MA Salafiyah students with a total of 19 students. The data obtained was then analyzed by changing the quantitative data into qualitative data using the scala rating guidelines. The results of this research and development show that scrapbook media is declared feasible and good for use based on validation from experts and students. Media expert validation results I accumulated from the aspect of media display and media programming showed a feasibility level of 70% with an average value of 3.5. While the validation results of media experts II (teachers) accumulated from the aspects of media display and media programming show a feasibility level of 68% with an average value of 3.4. Scientifically, the scrapbook media product in this study is proven to be acceptable and implemented in learning, especially learning to write biographical texts.